Youth sport - crowd-sourcing and talentsourcing - Drawer, S. (New Studies in Athletics, 2013)
Long a fundamental activity for sports organisations from clubs to national federations, the identification, confirmation and development of talented athletes has recently become increasingly sophisticated and a strategic `hot topic` in sport. With many nations having relatively small talent pools and a ever-growing number of sports demanding attention and participants, there is an increasing need to make the best of exiting talent across sports through strategic talent `transfer` initiatives or by adopting wider, broader and smarter ways of finding talent that may not reside in the various sports` natural development or competition pathways. Technology developments through social media crowdsourcing have the potential of providing novel ways that help identify individuals with the physical prerequisites and basic abilities for high-level performances in the future.